Construct Validity of Emotional Intelligence Scale for Sports Students - Yusuf Hidayat; Burhan Hambali; Dini Tresdani (Universitas Pendidikan Indonesia, 2022)
Emotional intelligence measurement is a potentially important construct and has become one of the most exciting issues in psychological research. This study aimed to test the construct validity of the emotional intelligence scale developed for sports students. The research employed a quantitative approach using a survey method. Participants involved in this study were 280 active sports students. Data were collected through an emotional intelligence scale and analyzed using factor analysis, namely exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) methods on Structural Equation Modeling (SEM) using AMOS 22 software. The fit index test model was based on three categories: absolute fit indices, incremental fit indices, and parsimony fit indices. It indicates that the scale met the valid and reliable criteria for measuring the emotional intelligence of sports students. There were 27 question items declared valid, meaning that all of these items measured the five components, including 14 indicators constructed according to the Bar-on conceptual model.